Strategi Pendidikan Karakter dalam Melahirkan Siswa Sekolah Dasar yang Inklusif dan Beretika - Bunga Cinta Syahputri; Indah Soviyanti; Putin Kasari (Jurnal Dharma PGSD, 2026)
This study aims to describe character education strategies that teachers can apply to produce elementary school students who are inclusive and ethical. Character education in elementary schools plays an important role in shaping students' tolerance, empathy, and responsibility, especially in diverse classrooms that accommodate children with special needs. This research uses a descriptive qualitative approach with a library research method, reviewing, comparing, and synthesizing various scientific sources such as journal articles, books, and previous studies relevant to character education, inclusive education, and student ethics. The results show that effective character education strategies for producing inclusive and ethical students include teacher role modelling, habituation of virtuous values, cross-ability collaborative learning, positive reinforcement, and the comprehensive involvement of parents and the school environment. The consistent application of these strategies has been shown to foster mutual respect for differences, empathy toward peers, and ethical behavior in social interaction within the school environment. Thus, inclusion-based character education needs to be planned and implemented in a sustainable manner so that elementary schools can produce a generation that is not only academically intelligent but also of good character, inclusive, and ethical.